Challenges to sustainable potato production in a changing climate: A research perspective - Quiróz, R.; Posadas, A.; Yarleque, C.; Heidinger, Haline; Barreda, C.; Raymundo, R.; Carbajal, M.; Tonnang, Henri E.Z.; Kroschel, Jürgen; Forbes, G.; Haan, Stef de (Springer, 2012)
Potato production systems face constant changes in climate conditions and the projections for the future indicate that changes in temperature and precipitation are expected in certain regions of the world. The impact will depend on what we do today to avoid negative consequences. Climate projections might have mixed repercussions on crops. Some crops and areas will benefit and some will be negatively impacted. These projections are difficult to implement in data scarce countries where surrogate data must be constructed. Themost likely temperature increases will not only have direct consequences on yield but are expected to produce an outburst of pest and diseases with consequences on productivity, use of toxic chemicals, and incorporating natural carbon sink locations into agriculture to guarantee food production. This might generate a vicious cycle that must be avoided. The challenge is to generate and promote appropriate technologies, management practices and policies that might not only maintain or increase yield but also reduce the dependency on incorporating more land into agriculture and the use of toxic chemicals that affect the environment and people’s health. The presentation will highlight some of the research the International Potato Center is conducting in developing countries, mainly on the development of tools and methods to better assess the challenges to sustainable potato production.